Exploring the Mechanism of Peroxodisulfate Activation with Silver Metavanadate to Generate Abundant Reactive Oxygen Species - Singh A.K.; Hollmann D.; Schwarze M.; Panda C.; Singh B.; Menezes P.W.; Indra A. (My University, 2025)
Reactive oxygen species (ROS) containing sulfate and hydroxyl radicals can act as Fenton type reagents to remove organic contaminants from water. Here, a catalytic system silver metavanadate is reported for the activation of peroxodisulfate in an aqueous medium to generate ROS, which is further utilized for the efficient degradation of the water-soluble pollutants such as phenols, pesticides, antibiotics, and organic dyes. Remarkably, complete carbon mineralization of the water-soluble contaminants is achieved to form carbon dioxide as the major product. In-situ electron paramagnetic resonance (EPR) studies combined with ex-situ methods reveal that a massive amount of hydroxyl radicals (•OH) are formed through sulfate radical anions (SO4•−) and act as the ROS for the organic pollutant degradation. In addition, the stability of the catalyst is monitored by various characterization techniques. © 2021 Wiley-VCH GmbH